Implementasi Accelerated Mobile Pages Untuk Sistem Informasi Manajemen Berbasis Web dan Absensi Pada Program Pendidikan Bahasa Universitas Kristen Petra - Stephen Lukas Wijaya; Justinus Andjarwirawan; Silvia Rostianingsih (Jurnal Infra, 2019)
Management Information System has become one of the mediaused to facilitate the administration, storing and viewing dataquickly and easily through Web. Nowadays, manualadministration requires more and less efficient resources,causing human error to affect important data.To answer the issue, a management information system is neededby utilizing website-based technology , assisted by AcceleratedMobile pages on the main page .By utilizing this technology, awebsite can be easily opened even in a slow internet connection.In addition, the presence of the website as a media managementinformation system facilitates the management of data, theadministration process of all parties in need in the languagecourse.From the research and testing systems that have been made, theapplication can help facilitate the process of administration anddata management. From the results of the questionnaireconducted on 10 respondents, the level of satisfaction with theprogram reached 3.1 on a scale of 4.